MEMBANGUN SENSE OF BELONGING (RASA MEMILIKI) INDIVIDU DAN MENERAPKANNYA SEBAGAI WUJUD MOTIVASI DIRI DALAM BEKERJA DAN KECINTAAN TERHADAP ORGANISASI PADA YPK DON BOSCO KAM - Maria, Elvie; Sudarso, Andriasan; Perangin-Angin, Johanes Terang Kita (Universitas Methodist Indonesia, 2023)
Sense of belonging is a something valuable that is owned by individuals in the organization when working. An understanding of diversity is not enough to build a positive work environment. It takes a strong sense of belonging to the organization by individuals as organizational human resources, so that a sense of responsibility and genuine effort is created in each individual's performance. Someone who has a sense of belonging will be able to act caring, attached, have empathy, be motivated and even be able to empower himself even without any encouragement. The seminar activity aims to grow and develop the knowledge, attitudes and skills for YPK Don Bosco KAM principal candidates, so that they are able to properly manage schools entrusted by the institution to them and support the success of improving the quality of learning in schools, building good social relations, which makes the school a second home for students, teachers and educational staff, and most importantly realizes that building a sense of belonging starts with oneself, from small things and to started from now, and applying it as description of self-motivation at work and applying it as description of self-motivation in work and love to the organization.